PENGEMBANGAN PERANGKAT PEMBELAJARAN MESIN FRAIS MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD YANG DIIMPLEMENTASIKAN PADA KURIKULUM 2013 - Marlan, Marlan; Susila, I Wayan; Basuki, Ismet (PENDIDIKAN VOKASI:TEORI DAN PRAKTIK, 2015)
Abstract This research is conducted since there is students? assumption of Vocational High School that the main learning process at school is only about practice, while the theory is only additional learning process. This interpretation can be seen from the students who do not pay attention if they are given the theory in their learning process. This assumption is strengthened by the learning process which is only conducted by direct learning through lecturing method. The purpose of this research is developing a instructional materials by using STAD cooperative learning model to solve those problems. It is expected to create the graduation of the vocational high school not only master in the skill but also in their cognitive and affective. It meets the message which is written in the 2013 curriculum. This research is a R&D development research. The steps use the theory of Borg and Gall which has been adapted. Each step uses 4D model from Thiagarajan. Those steps are primary study, draft model development, validity of the materials, and empirical test. The data collecting techniques used are observation, interview, expert validation, essay test, and questionnaire. The descriptive analysis is used as a technique to analyze the data. The result of the research shows that the research instrument gets the average score for 3.64 of a 1-4 rating scale, it is included in the valid criteria. The instructional materials consists of syllabus, lesson plan, students? worksheet, scoring rubric, learning media, and teachers book which get the average score for 3.76 of a 1-4 rating scale. The students? study accomplishment in the affective is 100%, cognitive is 93%, and skills is 100%. The implementation of the learning gets the score for 3.77 of a 1-4 rating scale. It is included in the very good category. The students? response in the learning process is positive. This result shows that the instructional materials which is develop is feasible to be used. Keys words: STAD Cooperative learning model, curriculum 2013, instructional materials.